INCLUSIVE EDUCATIONAL PRACTICES IN SARAWAK:A DECADE OF PROGRESS (2015-2025) - AN ANALYSIS OF PUBLISHED JOURNAL ARTICLES (Proceedings of International Conference on Special Education, 2025)
This study examines the development of special education and inclusive educational practices in Sarawak from 2015 to 2025 through a systematic review of published journal articles. The research aims to identify key trends, challenges, and innovations in the implementation of special and inclusive education policies, early intervention programs, special education services, teacher training initiatives, resource allocation, and instructional strategies. Using a qualitative content analysis approach, relevant academic publications were analyzed to assess the effectiveness of various initiatives in supporting students with special educational needs (SEN). Findings indicate that Sarawak has made significant progress in integrating students with disabilities into mainstream classrooms, driven by policy reforms, increased awareness, and professional development efforts. However, challenges such as inadequate teacher preparedness, limited resources, and socio-cultural barriers persist. The study highlights the role of individualized education plans, differentiated instruction, collaborative teaching strategies, and early intervention programs in enhancing student learning outcomes. This analysis provides insights into the successes and limitations of special and inclusive education implementation, offering recommendations for future policy improvements, teacher development programs, and the expansion of special education services in Sarawak.